Exploring the Impact of Family Environment, Locus of Control, and Adversity Quotient in Shaping Entrepreneurial Intentions among Students - Wijayanto, Sigit Ary; Ranto, Dwi Wahyu Pril; Sudarto, Sudarto (Journal of Business Management and Economic Development, 2025)
The current state of entrepreneurial motivation among students in Indonesia presents a noteworthy concern, as it appears to be relatively low, thus impacting the nation’s economic growth and employment prospects. This study seeks to explore the various factors influencing entrepreneurial intentions among college students, with a particular focus on family environment, locus of control, and adversity quotient. To conduct this research, we utilized a survey methodology, distributing questionnaires to 120 students from two esteemed Indonesian universities who have completed entrepreneurship courses and are actively involved in entrepreneurial initiatives. The findings revealed that family environment and adversity quotient exert a significant positive influence on students' entrepreneurial intentions, while locus of control did not show a substantial effect. These results emphasize the vital importance of family support and resilience in fostering entrepreneurial aspirations among university students. This research contributes meaningfully to the existing literature on entrepreneurship by illuminating the key roles of family environment and adversity quotient in shaping entrepreneurial intentions. It would be beneficial for future studies to further investigate the role of locus of control and to consider additional factors that may impact entrepreneurial intentions, thereby enriching our understanding of how to encourage entrepreneurial endeavors among students.